Adolescent fathers and mothers in the parenting exercise - Doris Amparo Parada-Rico; Carlos Iván García-Suárez (Universidad Francisco de Paula Santander, 2017)
Introduction: In general, parenting has been considered as the actions of socialization led by adults, which consider teenagers as unable people to achieve trajectories of the expected ideal development for girls and boys; on the other side the State despite of making progress about equity of these people, often turns their rights and necessities invisible. Materials and Methods: Through a systematic review of documents and databases such as cienceDirect, Scopus, Dialnet, Pubmed, Proquest, Adolec; information in Spanish, English and Portuguese of the last ten years was gathered with keywords: parenting practices and teenagers, teenage mothers-fathers, public policies in adolescence; this review returned 84 publications with the pointed aspects. Results: Perceptions of the adolescent mothers and fathers are identified, their social interactions in the parenting xercise, guidelines and practices of parenting and the contributions that regarding their recognition as adolescent parents, the State establishes. Conclusions: It is necessary to identify the perceptions in both adolescent fathers and mothers, and build jointly Public Politics that lead to the increase of support networks to assume the new tasks of care and continue with the activities that the models and social systems impose.